Détermination de l’âge dentaire en odontologie médico-légale - EL OSTA , Nada; EL OSTA , Lana (International Arab Journal of Dentistry (IAJD), 2014)
The study of the dentition is a common manner for age determination. In this article, we will discuss the pertinent methods to estimate the dental age of unknown dead or young alive people. In children, histological techniques as well as tooth eruption or calcification are appropriate to assess dental age in postmortem. After 15 years, it becomes difficult to estimate the age, since the phenomena related to the tooth eruption or calcification is completed. Therefore, the rate of racemization and Lamendin method are pertinent to determine the age adults in postmortem. Finally, in young alive people where age determination has legal interest, the mineralization of the wisdom tooth is a fundamental criterion for evaluating dental age. The determination of age depends on physiologic, environmental, genetic and pathologic factor. Thus, the age estimation in Lebanese population might be appraised using the methods universally adopted after adjustment, to obtain an accurate evaluation.